Réponses

Meilleure réponse !
2014-03-05T16:01:03+01:00
( le signe " * " est la multiplication )

A = 2*x
= 2*2
= 4

B = 4*x+5
= 4*2+5
= 13

C = 4*(x-3)*(x+8)
= 4*(2-3) * (2+8)
= (4*2 )+( 4*-3) *(2+8)
= 8+-12 *(2+8)
= -4*(2+8)
= -4*2 + -4*8
=-8 +-32
= -40

D = 3*x - 2 * (5*x-15)
= 3*2-2*(5*2-15)
= 6 - 2* (10-15)
= 6 - 2*10 + 2*-15
= 6 - 20 + -30
= -44

E = 9*x²
= 9*2²
= 9*4
= 36

F = 7-2*x
= 7-2*2
= 7-4
= 3

G = 2*(3*x-2)
= 2*(3*2-2)
= 2*(6-2)
= 2*6 + 2*-2
= 12 + -4
= 8

H = x*(x+2) -4*x
= 2*(2+2) -4*2
= 2*2 + 2*2 -2
=4 +4 -2
= 6

I = 4*x² - 2*x *(4-x)
= 4*2² - 2*2 (4-2)
= 16 - 4 (4-2)
= 16 - 16 + 8
=8

J = -3*x² + 5*x - 4
= -3*2² + 5*2 -4
= -12 + 10 - 4
= -6